Cold call: the acoustic repertoire of Ross Sea killer whales (Orcinus orca, Type C) in McMurdo Sound, Antarctica ... - Wellard, Rebecca; Pitman, Robert; Durban, John; Erbe, Christine (Dryad, 2020)
Killer whales (Orcinus orca) are top marine predators occurring globally. In Antarctic waters, five ecotypes have been described, with Type C being the smallest form of killer whale known. Acoustic recordings of nine encounters of Type C killer whales were collected in 2012 and 2013 in McMurdo Sound, Ross Sea. In a combined 3.5 hours of recordings, 6386 killer whale vocalisations were detected and graded based on their signal-to-noise ratio. Spectrograms of the highest-quality calls were examined for characteristic patterns yielding a catalogue of 28 call types (comprising 1250 calls). Acoustic parameters of each call were measured and summarised by call type. Type C killer whales produced complex calls, consisting of multiple frequency-modulated, amplitude-modulated and pulsed components. Often, two components occurred simultaneously, forming a biphonation; although the biphonic components did not necessarily start and end together, with one component lasting over several others. Addition and deletion of ... : Acoustic data were collected near the fast ice edge in McMurdo Sound, Ross Sea, Antarctica, between December 2012 and January 2013. The hydrophone was hand-deployed into the water at the ice edge in the immediate vicinity of killer whales (i.e., at < 100 m range) approximately 3-4 m below the surface. Acoustic recordings were obtained using an M-Audio Microtrack 24-96 recording unit with a Lab-Core LAB-40 hydrophone system (~5 Hz - 85 kHz bandwidth) and a 20 dB in-line amplifier. Sound was sampled at 96 kHz, 24 bit or 44.1 kHz, 24 bit, providing a bandwidth of 48 kHz and 22.05 kHz, respectively. Acoustic recordings were inspected both visually and aurally using acoustic software Raven Pro 1.5. Calls were visually graded based on their signal-to-noise ratio (SNR). Calls graded 2 and 3 were sorted into distinct categories to produce a call catalogue. ...